2008
DOI: 10.1177/1038411107086540.
|View full text |Cite
|
Sign up to set email alerts
|

Human resource practices and organizational commitment: A deeper examination

Abstract: This paper examines newer conceptualizations of HRM practices in the HR-performance relationship as well as newer conceptualizations of commitment. Juxtaposing these categories of HR practices and types of commitment provides a clearer theoretical rational for at least some ways that HR practices can influence organizational performance, be that positive or negative. Implications for research are then discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 71 publications
3
118
0
10
Order By: Relevance
“…Studies have shown that OC is one of the important aspects of understanding and predicting employees' work behavior and performance (Wright & Kehoe, 2008). Meyer (2009) indicated that OC is related to employees' physical and psychological well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that OC is one of the important aspects of understanding and predicting employees' work behavior and performance (Wright & Kehoe, 2008). Meyer (2009) indicated that OC is related to employees' physical and psychological well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although these practices are distinct, they are interrelated. To be effective in the accomplishment of the organizational goals and objectives, they have to be managed as a system (Wright & Kehoe, 2008). According to Dyer and Reeves (1995), HR practice bundles tend to yield sustainable performance outcomes than are individual practices.…”
Section: Human Resource Management (Hrm) Practicesmentioning
confidence: 99%
“…Hence, researchers interested in managing human capital have increasingly focused on human resource practices as instrumental in building the human capital that makes up resources and capabilities (Wright and Kehoe, 2008). Since firms are searching for means to develop sources of competitive advantage, investigators and experts have looked at firms' human resources (Wright et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These studies reveal that HRP have a positive effect on firm performance. Most of the literature on the relationships between HRP and firm performance explained the direct relationships of the practices on performance (Chan et al, 2004;Gooderhama et al, 2008;Guerrero and Didier, 2004;Lee et al, 2005;Liu and Chow, 2007;Mavondo et al, 2005;Ngo et al, 2008;Wood et al, 2006;Wright and Kehoe, 2008). Researchers have investigated the effects of HRP on organizational citizenship behaviours (OCBs) (Guest et al, 2004;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%